2017
DOI: 10.5847/wjem.j.1920-8642.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen degradation product levels on arrival for trauma patients requiring a transfusion even without head injury

Abstract: BACKGROUND:There have been few reports on the clinical significance of the fibrinogen degradation product (FDP) level in trauma patients with and without head injury. We retrospectively analyzed trauma patients with or without head injury to investigate the clinical signifi cance of the FDP level. METHODS:From April 2013 to June 2015, a medical chart review was retrospectively performed for all patients with trauma. The exclusion criteria included patients who did not receive a transfusion. The patients were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…However, the patient showed a markedly increased level of FDP, a biomarker used to predict the outcome in trauma patients [4][5][6]. Even when vital signs are stable and trauma is not very severe, a high FDP level on arrival may predict the need for transfusion or a poor outcome [4][5][6]. An FDP value exceeding 150 μg/ml on arrival suggests a potentially fatal outcome, so careful observation should be undertaken for such patients [6].…”
Section: Discussionmentioning
confidence: 99%
“…However, the patient showed a markedly increased level of FDP, a biomarker used to predict the outcome in trauma patients [4][5][6]. Even when vital signs are stable and trauma is not very severe, a high FDP level on arrival may predict the need for transfusion or a poor outcome [4][5][6]. An FDP value exceeding 150 μg/ml on arrival suggests a potentially fatal outcome, so careful observation should be undertaken for such patients [6].…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Regarding the mechanism underlying the positive correlation between the FDP level and the severity of trauma, an increase in the release of tissue factor, which causes fibrinolysis or the formation of a hematoma, depending on the severity of the trauma, might be involved. 3 The increase in the FDP level on arrival reflects coagulation abnormality after injury, 14 and it has been suggested that the increase in FDP is correlated with the amount of blood transfusion. 3,18 Fibrinogen is essential for clot formation and platelet aggregation; during major blood loss, fibrinogen decreases due to fibrinolysis to critically low levels earlier than the other coagulation factors.…”
Section: Discussionmentioning
confidence: 99%
“…3 The increase in the FDP level on arrival reflects coagulation abnormality after injury, 14 and it has been suggested that the increase in FDP is correlated with the amount of blood transfusion. 3,18 Fibrinogen is essential for clot formation and platelet aggregation; during major blood loss, fibrinogen decreases due to fibrinolysis to critically low levels earlier than the other coagulation factors. 2 Fibrinogen reduction due to fibrinolysis results in an increase in the FDP level and coagulopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in this study we calculated the ratios of FDP to fibrinogen, and of D-dimer to fibrinogen. Fibrinogen is said to be an independent risk factor of mortality and severity in blunt trauma patients [38][39][40], and a predictor of transfusion [41,42]. We combined the high FDP and D-dimer, and the low fibrinogen, to the ratio of FDP to fibrinogen and the ratio of D-dimer to fibrinogen, this was a novel finding.…”
Section: The Prediction Of Extravasation In Pelvic Fracture Using Coagulation Biomarkersmentioning
confidence: 93%